2009
DOI: 10.1038/onc.2009.410
|View full text |Cite
|
Sign up to set email alerts
|

Her2 activates NF-κB and induces invasion through the canonical pathway involving IKKα

Abstract: The membrane bound receptor tyrosine kinase Her2 is overexpressed in approximately 30% of human breast cancers which correlates with poor prognosis. Her2-induced signaling pathways include MAPK and PI3K/Akt, of which the latter has been shown to be critical for Her2+ breast cancer cell growth and survival. Additionally, the NF-κB pathway has been shown to be activated downstream of Her2 overexpression, however the mechanisms leading to this activation are not currently clear. Using Her2+/ER- breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
151
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(162 citation statements)
references
References 46 publications
(58 reference statements)
11
151
0
Order By: Relevance
“…Gene expression analysis of p65 knockdown cells led to a decrease in gene transcription levels of IL-6, IL-8, and TNF-a. (46) These data are consistent with our report as we observe the induction of all these cytokines and chemokines in addition to the accumulation of p65 in trastuzumabresistant cells. Moreover, our study also indicates that this induction of chemokine and cytokine levels is significantly sensitive to NF-kB inhibitor treatment, although there is marginal effect after lapatinib treatment.…”
Section: Mechanism Of Nf-jb Activation In Trastuzumab-resistant Cellssupporting
confidence: 82%
See 1 more Smart Citation
“…Gene expression analysis of p65 knockdown cells led to a decrease in gene transcription levels of IL-6, IL-8, and TNF-a. (46) These data are consistent with our report as we observe the induction of all these cytokines and chemokines in addition to the accumulation of p65 in trastuzumabresistant cells. Moreover, our study also indicates that this induction of chemokine and cytokine levels is significantly sensitive to NF-kB inhibitor treatment, although there is marginal effect after lapatinib treatment.…”
Section: Mechanism Of Nf-jb Activation In Trastuzumab-resistant Cellssupporting
confidence: 82%
“…(50) IKKa is involved in both canonical and noncanonical pathways. (46,51,52) Our data indicate that the canonical pathways, involving both IKKa and IKKb, are important for the activation of NF-kB in trastuzumabresistant BT-474-R cells. Silencing and overexpression of both IKK kinases will determine the role of this kinase individually in the development of resistance in the BT-474-R cell line.…”
Section: Mechanism Of Nf-jb Activation In Trastuzumab-resistant Cellsmentioning
confidence: 94%
“…It has been previously suggested that HER2-induced NFkB activation is mediated by AKT activation (8). However, a later study showed that AKT is not required for the HER2-induced NF-kB activation (5). The same study further suggested that HER2 activates NF-kB through a canonical pathway that depends on IKKa, a component of IKK complex (5).…”
Section: Introductionmentioning
confidence: 79%
“…However, a later study showed that AKT is not required for the HER2-induced NF-kB activation (5). The same study further suggested that HER2 activates NF-kB through a canonical pathway that depends on IKKa, a component of IKK complex (5). However, the molecular link between HER2 and the IKK complex still remains to be determined.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation